Peripheral Macrophages Promote Tissue Regeneration in Zebrafish by Fine-Tuning the Inflammatory Response - Morales, Rodrigo A.; Allende, Miguel L. (Frontiers in Immunology, 2019)
The role of macrophages during regeneration in zebrafish has been well documented. Nevertheless, new evidence indicates that zebrafish macrophages are a heterogeneous population of cells, and that they can play different roles during immune responses and in tissue restoration after damage and infection. In this work, we first aimed to classify zebrafish macrophages according to their distribution in the larva during homeostasis and after tissue damage, distinguishing peripheral and hematopoietic tissue resident macrophages. We discovered differences between the migratory behavior of these two macrophage populations both before and after tissue damage, triggered by the amputation of the tail fin. Further, we found a specific role for peripheral tissue-resident macrophages, and we propose that these cells contribute to tail fin regeneration by down-regulating inflammatory mediators such as interleukin-1b (il1b) and by diminishing reactive oxygen species (ROS) in the damage site. Our work suggests that specific macrophage populations recruited after tissue damage in zebrafish larvae can display different functions during both inflammation and tissue regeneration.